Improving rapid pathogen detection: towards a gram-selective lateral flow test - Crossland, James (The University of Edinburgh, 2024)
The development of rapid detection assays, such as lateral flow tests, have been effective in helping to detect a range of biological targets, most recently in the COVID-19 pandemic. The effective detection and classification of bacteria, such as their Gram status using rapid low-cost lateral flow assay could help diagnose and target treatment of bacterial infections in medical and veterinary applications. This is important as over prescription of broad-spectrum antibiotics is a well-known contributor to the rise in antimicrobial resistance. My work targeted the development of lateral flow assays to achieve the specific detection of Gram-negative bacteria. To make the assay Gram selective, targeting/binding ligands were synthesised based on Polymyxin B, a Gram-negative selective antibiotic. A literature method of selective functionalisation of Polymyxin B was optimised to service material at the gram scale for the development of three Polymyxin conjugates: a Lipoic acid-Polymyxin conjugate and two Biotin-Polymyxin conjugates with and without a spacer. The most effective binding/labelling agent was determined to be a Biotin-Polymyxin conjugate with a six-carbon spacer, which allowed the fluorescently labelling of E. coli by the generation of a Bacteria-Polymyxin-Biotin-Streptavidin-fluorophore sandwich. Most lateral flow tests use gold nanoparticles to label the target analyte as it provides an intense red colour that is easily detectable by eye, and this was replicated here by the attachment of Polymyxin to gold nanoparticles. Through testing a range of methods for the attachment of Polymyxin, a nanoparticle system that could be used to selectively label the surface of bacteria was developed. This Polymyxin-nanoparticle labelling system was characterised via electron microscopy. Nitrocellulose membranes were laser cut to shape and printed with reagents to give a strip assay platform that could analyse the behaviour of the synthesised gold nanoparticles and the Polymyxin targeting agents in flow. 3D printing was used to fabricate an imaging enclosure to enable repeatable imaging that allowed for smartphone capture of the assays and analysis with a custom Python-based image analysis script. This allowed high-throughput testing and optimisation of the assay and flow conditions. Through the optimisation of the lateral flow assay design Gram-negative E. coli were able to be detected in flow, imaged, and analysed. My PhD work thus provides an example of a lateral flow assay functioning without antibodies or aptamers. This work could provide the foundation for further development, including other antibiotics to target different bacteria.
Keywords: rapid pathogen detection; gram-selective lateral flow test; lateral flow tests; Gram selective; targeting/binding ligands; Gram-negative selective antibiotic; Polymyxin B; Lipoic acid-Polymyxin conjugate; Biotin-Polymyxin conjugates; Biotin-Polymyxin conjugate; Biotin-Polymyxin conjugate with a six-carbon spacer; Bacteria-Polymyxin-Biotin-Streptavidin-fluorophore sandwich; gold nanoparticles; attachment of Polymyxin to gold nanoparticles; Polymyxin-nanoparticle labelling system; Nitrocellulose membranes; Gram-negative E. coli